مصطلح التّداولية: إشكالات الوضع والاستعمال في الدّرس اللّساني العربي - حمو الحاج, ذهبية (University of Eloued جامعة الوادي, 2018)
لقد استطاعت التّداولية أن تفرض نفسها في التّفكير اللّساني العربي علمًا ومنهجًا ونظريةً ومصطلحًا، مثلما فرضت اللّسانيات نفسها في القرن العشرين. لقد تمكّن اللّسانيون العرب من تبنّي الدّرس اللّساني الغربي وتقليده بكلّ معالمه، واستطاعوا بفضله أن يطوّروا اللّغة العربية من حيث الدّراسات والمناهج. ظهرت التّداولية في الفكر الغربي مواكبة للتّفكير الفلسفي مع فلاسفة أكسفورد، مثلما ظهرت في الضّفة الأخرى لتُعيد النّظر في الدّرس اللّساني السوسوري، وتبلور ذلك عند "إميل بنفنست" في حديثه عن مشاكل اللّسانيات العامّة، ونشأ إثر ذلك ما يدعى باللّسانيات التّداولية، التي أثارت قضايا هامّة من قبيل الذّات المتلفّظة، الضمائر، السياق، الإنية التلفظية....واتّسعت بفضلها رقعة التّحليل اللّغوي، الذي طال الخطابات بشتى أنواعها...فأصبحنا نتحدّث عن منهج عام يُستثمر في كلّ ما يرتبط باستعمال اللّغة في سياق معيّن، وذلك بفضل أدواته الإجرائية وآلياته وتقنياته التي تستند إلى علوم شتّى كعلم النّفس، وعلم الاجتماع، والفلسفة، والمنطق، واللّسانيات....والجدير بالملاحظة أنّ الدّرس التّداولي لقي اهتماما كبيرا من لدن الدّارسين العرب إلى حدّ اقتحام الجوانب الذّهنية المعرفية، والذّكاء الصناعي، وعلم النّفس المعرفي، والعلوم المعرفية بشكل عام Paragmatics has been able to impose itself in Arabic linguistic thinking on the level of methodology, theory and terminology as linguistics did in the twentieth century. The Arab Linguals managed to adopt the Western linguistic lesson and imitate it with all its features. So they were able to develop Arabic language in studies and methods. Paragmatics has appeared in Western thought, keeping the philosophical thinking of Oxford philosophers as it appeared in the other side in order to reconsider De Saussure linguistic lesson. This was cleared by "Emil Benvenist" in his talk about the problems of general linguistics, and as a result Paragmatics linguistics has appeared that discussed important issues such as pronouns, context and so on.It Hence, linguistic analysis has been expended and reached all kinds of speech... So we are talking about a general approach that is related to the use of language in a particular context thanks to its procedural mechanisms and techniques that are based on various sciences such as psychology, sociology, philosophy, logic and linguistics. It is worth noting that the pragmatism have received a great attention from Arab researcher till the extent of finding out the intellectual aspects of cognitive, industrial intelligence, cognitive psychology, and cognitive science in general viewpoint.
Keywords: اللّغة، التّداولية، اللّسانيات، المصطلح، الاستعمال; language, Paragmatics, linguistics, term, use